Effects of the Sport Education Model on University Students Game Performance and Content Knowledge in Basketball - Layne, Todd E; Yli-Piipari, Sami (Journal of Sports Research, 2015)
Many universities offer an abundant amount of physical activity courses designed to improve student knowledge and performance which may lead to increased fitness involvement. This study examined the effect of Sport Education model on university students’ (N = 25, 22 males, 3 females) basketball game performance and content knowledge of a physical activity course. Students were taught using either the Sport Education instructional model or a traditional method of teaching basketball. Data were collected to determine game efficiency through the examination of game statistics, offensive game performance measured by the basketball offensive game performance instrument, and content knowledge through the completion of a pre-and-post examination. Results revealed that students in the Sport Education group improved significantly in their offensive game performance and content knowledge compared to a traditional teaching model. In addition, the game efficiency of the Sport Education group did slightly improve while the students in the traditional group did experience a decrease. These findings suggest that the Sport Education model is an effective pedagogical approach for improving game performance and sport content knowledge of university students. Based on the limited amount of research on the impact of the Sport Education model with university physical activity courses, future studies should continue to examine the effectiveness of the model.